PENGARUH MODEL CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII - Peni Apriyanti; Hari Sumardi; Hanifah Hanifah (Universitas Bhinneka PGRI, 2025)
Mathematical problem-solving skills are competencies required by students to face challenges both in academic settings and real-life situations. However, based on observations, these skills are still considered low, including at SMPIT Rabbani in Bengkulu City. The research was conducted to examine the effect of implementing the CORE model on the mathematical problem-solving abilities of eighth-grade students at SMPIT Rabbani, Bengkulu City, using the topic of linear equations. The research design used is a quasi-experimental design, with an experimental group of 13 students applying the CORE model, and a control group of 13 students applying the conventional method. Data analysis showed a significance value (2-tailed) of 0.048 (0.05) with a Cohen’s d value of 0.85, indicating a significant impact with a large effect size. Finding of the search suggest that students who were taught using the CORE model demonstrated better problem-solving abilities than those taught using the conventional method, thus proving that this model is effective in improving students' mathematical problem-solving skills.